(untitled) (Journal of Scientific Research, 2022)
In this paper, the problem of unsteady two-dimensional boundary layer heat and mass transfer flow over an exponentially stretching sheet embedded in a porous medium in the presence of a uniform magnetic field with thermal radiation, heat generation/absorption, and suction/blowing is analyzed numerically. Instead of no-slip boundary conditions, velocity slip, thermal slip, and mass slips at the boundary are considered. Using a suitable similarity transformation, the governing partial differential equations are transformed to a system coupled with nonlinear ordinary differential equations. The reduced equations are solved numerically by using bvp4c with the MATLAB package. A detailed parametric study is performed to illustrate the physical parameters on the velocity, temperature, and concentration profile and the local skin-friction coefficient and Nusselt and Sherwood number. Then the results are exhibited in both graphical and tabular forms. It is observed that the present results have been in close agreement with the previously published studies under some special cases.